International Diversification, Ownership Structure and Performance in an Emerging Market: Evidence from Chile - Espinosa-Mendez, C; Gorigoitia-Gallardo, J (Taylor and Francis Ltd., 2021)
This research analyzes the impact of international diversification on the performance of Chilean exporting firms. Considering a sample of 47 companies listed on the Santiago Stock Exchange during the period 2003–2013, we found an international diversification discount. Secondly, when investigating the relationship between international diversification and performance, we found that they are related through an inverted U curve. Finally, we investigated how the ownership structure moderates the relationship between international diversification and performance, finding that the ownership concentration and pyramidal ownership positively impacts the performance of companies initiating international diversification strategies; and that the business groups’ affiliation negatively impacts in the international diversification-performance relationship. © 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.